The Pros and Cons of Preserving a Functioning Arteriovenous Fistula after Kidney Transplantation. Issue 1 (March 2016) - Voorzaat, Bram M.; van Schaik, Jan; Siebelink, Hans-Marc J.; Tordoir, Jan H.; Rotmans, Joris I.
The autologous arteriovenous fistula (AVF) for hemodialysis burdens the cardiovascular system with increased cardiac output and pulmonary artery pressure, increasing cardiovascular risk. This article reviews literature on the benefits and drawbacks of a functioning AVF after kidney transplantation and discusses the cardiovascular effects of AVF closure. Several cohort studies demonstrate a significant cardiac burden of an AVF and improvement of cardiac dimensions after AVF ligation. However, no randomized trials have been conducted on routine AVF closure after successful kidney transplantation. Therefore, clinical trials are warranted to evaluate whether the cardiovascular benefits of routine AVF closure outweigh the potential harm for patients after successful kidney transplantation.